TRADITIONAL VALUES IN THE FUNCTION OF PROMOTION OF ŠUMADIJA AND POMORAVLJE AS RURAL TOURISM DESTINATIONS - Mandarić, Marija; Milicević, Snežana; Sekulić, Dejan (Economics of Agriculture, 2017)
Rural tourism and diversifcation of economic activities are now an integral part of sustainable development of rural areas and regions of Šumadija and Pomoravlje. Development of rural tourism improves the economic position and social activity of the population of rural areas. Šumadija and Pomoravlje region has signifcant natural and human resources for the development of rural tourism, which have not been adequately utilized. The preservation of authentic values of climate, especially of traditional crafts and gastronomy, can contribute to the development and recognition of the region as a new destination for rural tourism in Serbia. Traditional products due to their features, quality and heritage, can become a regional brand, and also promote the region as a unique destination of rural tourism. The aim of the paper is to explore the representation of traditional crafts, production of handicrafts and traditional cuisine in the region of Šumadija and Pomoravlje. The results of the research conducted point to a signifcant and under-utilized potential of traditional values in the development and promotion of the region as a rural tourism destination.